Pengaruh Penambahan Zat Aditif Pada Campuran Bahan Bakar Bensin – Bioethanol Terhadap Specific Fuel Consumption - Monasari, Ratna; Firdaus, Ahmad Hanif; Qosim, Nanang (UNIVERSITAS PENDIDIKAN GANESHA, 2021)
Pemanfaatan energi terbarukan di Indonesia masih tergolong rendah dibandingkan dengan sumber energi tak terbarukan dari minyak bumi, batu bara, maupun gas alam. Dengan jumlah energi tak terbarukan yang terbatas mendorong untuk mengembangkan penggunaan bahan bakar alternatif. Saat ini bioetanol merupakan salah satu bahan bakar alternatif yang sedang dikembangkan sebagai pengganti maupun campuran bahan bakar bensin, yang dikenal sebagai etanol anhidrat yang memiliki konsentrasi diatas 96%. Campuran bioetanol memberikan pengaruh terhadap peningkatan bilangan oktan dan mampu mengurangi emisi gas buang yang dihasilkan. Untuk mendapatkan efek yang lebih optimal dalam konsumsi bahan bakar zat aditif seperti oxygenated cyclohexanol ditambahkan pada campuran bahan bakar. Studi dilakukan pada perbandingan bahan bakar E5 sampai E15 dengan penggunaan aditif tersebut. Pengujian konsumsi bahan bakar dilakukan pada mesin satu silinder spark ignition dengan posisi bukaan throttle 100%. Terdapat sensor pada bagian tanki bahan bakar untuk menghitung specific fuel consumption (SFC) dengan variasi kecepatan mesin. Penelitian ini bertujuan untuk melihat pengaruh penambahan zat aditif pada campuran bahan bakar terhadap konsumsi bahan bakar.Kata kunci: bensin; bioetanol; emisi gas buang; zat aditif.The use of renewable energy in Indonesia is still low compared to non-renewable energy sources from petroleum, coal, and natural gas. The limited amount of non-renewable energy encourages developing the use of alternative fuels. Currently, bioethanol is an alternative fuel that is being developed as a substitute or mixture of gasoline fuel, known as anhydrous ethanol which has a concentration above 96%. The bioethanol mixture has an effect on increasing the octane number and is able to reduce the resulting exhaust gas emissions. To get a more optimal effect on fuel consumption, additives such as oxygenated cyclohexanol are added to the fuel mixture. Studies were carried out on the comparison of fuel E5 to E15 with the use of these additives. The fuel consumption test was carried out on a single-cylinder spark-ignition engine with a 100% throttle opening position. There is a sensor on the fuel tank to calculate the specific fuel consumption (SFC) with variations in engine speed. This study aims to determine the effect of adding additives to the fuel mixture on fuel consumption.Keywords : fuel; bioethanol; exhaust gas emissions; additives. DAFTAR RUJUKANAbikusna, S., Sugiarto, B., & Suntoro D. (2017). Low Grade Bioethanol for Fuel Mixing on Gasoline Engine Using Distillation Process. in AIP Conference Proceedings. AIP Publishing.Abikusna, S. (2018). The Effect of Additive on Combustion Characteristics and Cycle to Cycle Variations on SI Engine Fueled by Gasoline and Bioethanol, Technology organic and inorganic substances. P. 27-37. Doi: 10.15587/1729-4061.2018.147585Abikusna, S., B. Sugiarto, & Zulfan, A. (2017). Fuel consumption and emission on fuel mixer low-grade bioethanol fuelled motorcycle. in MATEC Web of Conferences. EDP Sciences.Costa, R. C., & Sodré, J.R. (2011). Compression ratio effects on an ethanol/gasoline fuelled engine performance. Applied Thermal Engineering, 31(2): p. 278-283.de Melo, T.C.C., et al., 2012. Hydrous ethanol–gasoline blends–Combustion and emission investigations on a Flex-Fuel engine. Fuel, 97: p. 796-804.Costa, R.C. & Sodré, J.R. (2009) . Hydrous Ethanol Vs. Gasoline-Ethanol Blend: Engine Performance and Emissions. International Journal of FuelGao, J. D. J., & Huang, Z. (2007). Spray Properties of Alternative Fuels: A Comparative Analysis of Ethanol–Gasoline Blends and Gasoline. Fuel. 86(10): p. 1645-1650.Keith, O., & Trevor, C. (1995). Automotive fuels reference book. Society of Automotive Engineers, Inc. Warrendale, p. 487.Gholamhassan, N. B. G., Yusaf, T. Safieddin, S. M., & Ardebili, R.M. (2015). Optimization of performance and exhaust emission parameters of a SI (spark ignition) engine with gasoline-ethanol blended fuels using response surface methodology. Elsevier, energy xxx: p. 15.Jang, S. H., & Choi, J. H. (2016). Comparison of fuel consumption and emission characteristics of various marine heavy fuel additives. Applied Energy, 179, 36–44. https://doi.org/10.1016/j.apenergy.2016.06.122Monasari, R., Abikusna, S., Sugiarto, B., & Ajiseno, B. (2018). IOP Conference Series: Earth and Environmental Science Analysis of emission gas and fuel consumption on SI engine fueled with low-grade bioethanol and oxygenated cycloheptanol additive Analysis of emission gas and fuel consumption on SI engine fueled with low-grade bioethanol and oxygenated cycloheptanol additive. 105, 12058. https://doi.org/10.1088/1755-1315/105/1/012058Srinivasan, C. A., & Saravanan, C. (2010). Study of Combustion Characteristics of an SI Engine Fuelled with Ethanol and Oxygenated Fuel Additives. Journal of Sustainable Energy & Environment. 1(2): p. 85-91.Sugiarto, B. (2002) Motor Pembakaran Dalam. Jakarta: Universitas Indonesia. ISBN 979- 97726-7-2.Thangavelu, S. K., Ahmed, A. S., & Ani, F. N. (2016). Review on Bioethanol as Alternative Fuel for Spark Ignition Engines. Renewable and Sustainable Energy Reviews. 56: p. 820-835Zhao, L., Wang, X., Wang, D., & Su, X. (2020). Investigation of the effects of lean mixtures on combustion and particulate emissions in a DISI engine fueled with bioethanol-gasoline blends. Fuel, 260, 116096. https://doi.org/10.1016/j.fuel.2019.116096